Variation and Context of Yawns in Captive Chimpanzees (Pan troglodytes) - Vick, Sarah-Jane (2010)
Primate yawns are usually categorised according to context (e.g. as a threat, anxious or rest yawn) but there has been little consideration of whether these yawns are best regarded as a unitary behaviour that only differs with respect to the context in which it is observed. This study examined the context and precise morphology of yawns in a group of 11 captive chimpanzees. Focal video sampling was used to describe the morphology and intensity of 124 yawns using ChimpFACS, a system for coding facial movements. Two distinct forms of yawn were identified, a full yawn and a yawn which is modified by additional actions which reduce the mouth aperture. These modified yawns may indicate some degree of voluntary control over facial movement in chimpanzees and consequently multiple functions of yawning according to context. To assess context effects, mean activity levels (resting, locomotion and grooming) and scratching rates were compared one minute before and after each yawn. Locomotion was significantly increased following both types of yawn, while scratching rates significantly increased following modified yawns but decreased following full yawns. In terms of individual differences, males did not yawn more than females although male yawns were of higher intensity, both in the degree of mouth opening and in the amount of associated head movement. These data indicate that yawning is associated with a change in activity levels in chimpanzees but only modified yawns may be related to increased arousal. Different types of yawn can therefore be differentiated at the morphological level as well as context level.